w+6=

Simple and best practice solution for w+6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for w+6= equation:


Simplifying
w + 6 = 0

Reorder the terms:
6 + w = 0

Solving
6 + w = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + w = 0 + -6

Combine like terms: 6 + -6 = 0
0 + w = 0 + -6
w = 0 + -6

Combine like terms: 0 + -6 = -6
w = -6

Simplifying
w = -6

See similar equations:

| -4(-2+a)=52 | | x/(x-3)=8 | | 12x/(-4x) | | -5(m-5)=-60 | | a+-3+3=-2 | | 2.9(-5-1)-4.4(-5-7)= | | 175m-75m+58500=60300-200m | | x(3+3)=64.5 | | 7(2h-4)+3h=108 | | x(2+2)=64.5 | | 2.5x+0.5x=5+3.5x | | 360-(13x)=114 | | x(2+2)=43 | | x+2+2=43 | | 3/4×36 | | (8+3x+5x^2+8x^3)+(5-3x+5x^2-8x^3)= | | 12x-34=85-5x | | 4x=2y-4-20 | | 7(5x-2)=6(6x-1)x | | 16=7x-33 | | -1+5y=-16 | | 5r^2-44r+120=-30+111r | | -9+6b=9+3b | | 36+(24)3= | | -15=6+7y | | 4x+5+5x+22=90 | | (X/5)=-13 | | 4k=6k-6 | | 4k=6k-2 | | 48.3(8/25)2 | | a+2=-12 | | 3y+2=y+11 |

Equations solver categories